Peningkatan Pengetahuan Petani Porang tentang Pembudidayaan dan Pengolahan Hasil Tanaman Porang di Desa Sungai Alang Kecamatan Karang Intan: Increasing Porang Farmers’ Knowledge about Cultivation and Processing of Porang Crops in Sungai Alang Village, Karang Intan District - Anggraini, Alya Jennita; Wulandari, Retno Nur; Uzma, Sopiana; Rusnadi, Muhamad; Hidayat, Wahyu; Hardarani, Nofia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The porang plant has many benefits and has a high selling price, so farmers need to cultivate porang well to get maximum results. Apart from cultivation, processing of porang plants in the form of tubers also needs to be done. The selling price for porang tubers that have been processed into food products will be higher. This counseling discussed cultivation and processing techniques for porang plants because many porang farmers do not know optimal cultivation and processing techniques. Cultivation of porang plants regarding planting, fertilizing, maintaining, or processing the tubers needs to be done well. However, farmers’ lack of knowledge regarding the cultivation and processing of porang results causes the harvest to not be optimal and farmers can only sell fresh porang tubers. The method implemented in this community service activity was through providing materials, questionnaires before counseling, and questionnaires after counseling, as well as questions and answers between participants and presenters. The results of the questionnaire showed that this extension was successful in adding new insights to farmers. Most respondents hope that there will be similar outreach in the future to improve their knowledge and skills.